The sassy belles - Albright, Beth.
There are only two seasons in Tuscaloosa--football and waiting-for-football. When Lewis Heart, football announcer and voice of the Crimson Tide, vanishes after an impromptu romp with Vivi Ann McFadden at the Fountain Mist Motel, Vivi does what any Southern woman would do: call her best friend, Blake O'Hara Heart, attorney-at-law.
Keywords: Women -- Alabama -- Tuscaloosa -- Fiction; Female friendship -- Fiction; Missing persons -- Fiction